The Impact Of Online System on Health During Covid 19: A Comprehensive Study - Bhupesh Rawat; Ankur Singh Bist; Untung Rahardja; Chandra Lukita; Dwi Apriliasari (ADI Publisher, 2022)
COVID-19 creates an unprecedented situation before humanity. Covid-19 has changed lives in all aspects, from education, industry and social life. However, the existence of Covid-19 has greatly impacted the field of education, where the applicable learning methods usually need to make drastic changes to decide the spread of Covid-19. The education sector is turning to online education because it is not possible to call students in schools and colleges. Technology online education is proving itself to be a cure for catastrophe and filling gaps. There are major challenges regarding student health due to the high use of mobile, tablet and computer screens. There are problems regarding student health in the application of technology online learning, in this paper we make a detailed study of the same problem with the ultimate goal of research to find out the preventive measures. In this paper, we use the literature study method to explore negative cases in terms of obtaining negative reasoning due to excessive screen use during the COVID-19 scenario